2020
DOI: 10.1101/2020.02.02.931204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fast Transport of RNA Granules by Direct Interactions with KIF5A/KLC1 Motors Prevents Axon Degeneration

Abstract: 20Complex neural circuitry requires stable connections formed by lengthy axons. To maintain these 21 functional circuits, fast transport delivers RNAs to distal axons where they undergo local translation. 22However, the mechanism that enables long distance transport of non-membrane enclosed organelles 23 such as RNA granules is not known. Here we demonstrate that a complex containing RNA and the RNA-24 binding protein (RBP) SFPQ interacts directly with a tetrameric kinesin containing the adaptor KLC1 and 25 th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…This coiled-coil interaction allows for movement of cargo proteins, lipids, and RNAs within membrane-bound and membraneless organelles via motor protein binding, along the microtubule cytoskeletal network. For example, the microtubule-associated kinesin-1 cargo adaptor complex (KLC1) moves ribonucleoprotein granules by interacting with the RBP SFPQ via a coiled-coil motif, an interaction that is necessary for axonal transport (Fukuda et al, 2020). Large, membrane-bounded organelles, such as the lysosome, can be trafficked throughout the cell via similar coiled-coil protein-protein interactions.…”
Section: Coiled-coil Domains Are Over-represented In Rna-binding Protmentioning
confidence: 99%
“…This coiled-coil interaction allows for movement of cargo proteins, lipids, and RNAs within membrane-bound and membraneless organelles via motor protein binding, along the microtubule cytoskeletal network. For example, the microtubule-associated kinesin-1 cargo adaptor complex (KLC1) moves ribonucleoprotein granules by interacting with the RBP SFPQ via a coiled-coil motif, an interaction that is necessary for axonal transport (Fukuda et al, 2020). Large, membrane-bounded organelles, such as the lysosome, can be trafficked throughout the cell via similar coiled-coil protein-protein interactions.…”
Section: Coiled-coil Domains Are Over-represented In Rna-binding Protmentioning
confidence: 99%
“…Microdissection and TRAP approaches for isolating RNA have revealed important roles for transcript UTR sequence motifs and transcript trafficking proteins in local translation. mRNAs are transported in phase-separated ribonucleoprotein (RNP) granules over long distances to dendrites and axons to establish local transcriptome pools (Nalavadi et al, 2012;Jung et al, 2014;Das et al, 2019;Liao et al, 2019;Pushpalatha and Besse, 2019;Fukuda et al, 2020;Rhine et al, 2020;Wu et al, 2020; Figure 3). The spatial control of transcript trafficking is based on mRNA sequences found in 3 and 5 untranslated regions (UTRs; Figure 3A) that act as binding sites for trans-acting RBPs (Sahoo et al, 2018;Bae and Miura, 2020).…”
Section: Local Transcriptomes/translatomes Are Precisementioning
confidence: 99%
“…More recently, it has been demonstrated that a complex containing RNA and SFPQ directly interacts with a tetrameric kinesin complex containing the motor, KIF5A, and the adaptor, KLC1 [ 59 ], further evidencing the SFPQ-dependent mRNA transport in neurons. Defects in kinesin-driven transport of SFPQ led to axon degeneration in the dorsal root ganglion sensory neurons, indicating that the interaction of SFPQ with the kinesin motor complex sustains axon survival by transporting relevant mRNA towards the distal end of the dorsal root ganglion sensory neurons for translation.…”
Section: Sfpq In Neuronal Development and Maintenance Of Neuronal mentioning
confidence: 99%
“…Defects in kinesin-driven transport of SFPQ led to axon degeneration in the dorsal root ganglion sensory neurons, indicating that the interaction of SFPQ with the kinesin motor complex sustains axon survival by transporting relevant mRNA towards the distal end of the dorsal root ganglion sensory neurons for translation. Interestingly, the authors found that the interaction of the kinesin motor complex and SFPQ is RNA-dependent, suggesting that KIF5A/KLC1 bind and transport SFPQ when it is part of large RNP transport granules [ 59 ].…”
Section: Sfpq In Neuronal Development and Maintenance Of Neuronal mentioning
confidence: 99%